At Westonci.ca, we connect you with the answers you need, thanks to our active and informed community. Get immediate and reliable solutions to your questions from a knowledgeable community of professionals on our platform. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.
Sagot :
To solve the system of equations given by
[tex]\[ \begin{cases} x - y = 7 \\ x^2 + y = 149 \end{cases} \][/tex]
we will use substitution and solve these step-by-step.
1. Express [tex]\( y \)[/tex] in terms of [tex]\( x \)[/tex] from the first equation:
[tex]\[ x - y = 7 \implies y = x - 7 \][/tex]
2. Substitute this expression for [tex]\( y \)[/tex] into the second equation:
[tex]\[ x^2 + (x - 7) = 149 \][/tex]
Simplify the equation:
[tex]\[ x^2 + x - 7 = 149 \][/tex]
Combine like terms:
[tex]\[ x^2 + x - 156 = 0 \][/tex]
3. Solve the quadratic equation:
[tex]\[ x^2 + x - 156 = 0 \][/tex]
To solve this quadratic equation, we can factorize it. We need to find two numbers that multiply to [tex]\(-156\)[/tex] and add up to [tex]\(1\)[/tex].
These numbers are [tex]\(13\)[/tex] and [tex]\(-12\)[/tex]. Hence, we factorize:
[tex]\[ x^2 + 13x - 12x - 156 = 0 \][/tex]
Group the terms:
[tex]\[ x(x + 13) - 12(x + 13) = 0 \][/tex]
Factor by grouping:
[tex]\[ (x - 12)(x + 13) = 0 \][/tex]
4. Find the zeroes of the factored equation:
[tex]\[ x - 12 = 0 \implies x = 12 \][/tex]
[tex]\[ x + 13 = 0 \implies x = -13 \][/tex]
5. Substitute these [tex]\( x \)[/tex]-values back into the expression [tex]\( y = x - 7 \)[/tex] to find the corresponding [tex]\( y \)[/tex]-values:
For [tex]\( x = 12 \)[/tex]:
[tex]\[ y = 12 - 7 = 5 \][/tex]
For [tex]\( x = -13 \)[/tex]:
[tex]\[ y = -13 - 7 = -20 \][/tex]
6. Write down the solutions:
The solutions to the system are:
[tex]\[ (x, y) = (12, 5) \quad \text{and} \quad (x, y) = (-13, -20) \][/tex]
So, the system of equations has two solutions:
[tex]\[ (x, y) = (12, 5) \quad \text{and} \quad (x, y) = (-13, -20) \][/tex]
[tex]\[ \begin{cases} x - y = 7 \\ x^2 + y = 149 \end{cases} \][/tex]
we will use substitution and solve these step-by-step.
1. Express [tex]\( y \)[/tex] in terms of [tex]\( x \)[/tex] from the first equation:
[tex]\[ x - y = 7 \implies y = x - 7 \][/tex]
2. Substitute this expression for [tex]\( y \)[/tex] into the second equation:
[tex]\[ x^2 + (x - 7) = 149 \][/tex]
Simplify the equation:
[tex]\[ x^2 + x - 7 = 149 \][/tex]
Combine like terms:
[tex]\[ x^2 + x - 156 = 0 \][/tex]
3. Solve the quadratic equation:
[tex]\[ x^2 + x - 156 = 0 \][/tex]
To solve this quadratic equation, we can factorize it. We need to find two numbers that multiply to [tex]\(-156\)[/tex] and add up to [tex]\(1\)[/tex].
These numbers are [tex]\(13\)[/tex] and [tex]\(-12\)[/tex]. Hence, we factorize:
[tex]\[ x^2 + 13x - 12x - 156 = 0 \][/tex]
Group the terms:
[tex]\[ x(x + 13) - 12(x + 13) = 0 \][/tex]
Factor by grouping:
[tex]\[ (x - 12)(x + 13) = 0 \][/tex]
4. Find the zeroes of the factored equation:
[tex]\[ x - 12 = 0 \implies x = 12 \][/tex]
[tex]\[ x + 13 = 0 \implies x = -13 \][/tex]
5. Substitute these [tex]\( x \)[/tex]-values back into the expression [tex]\( y = x - 7 \)[/tex] to find the corresponding [tex]\( y \)[/tex]-values:
For [tex]\( x = 12 \)[/tex]:
[tex]\[ y = 12 - 7 = 5 \][/tex]
For [tex]\( x = -13 \)[/tex]:
[tex]\[ y = -13 - 7 = -20 \][/tex]
6. Write down the solutions:
The solutions to the system are:
[tex]\[ (x, y) = (12, 5) \quad \text{and} \quad (x, y) = (-13, -20) \][/tex]
So, the system of equations has two solutions:
[tex]\[ (x, y) = (12, 5) \quad \text{and} \quad (x, y) = (-13, -20) \][/tex]
Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. Westonci.ca is committed to providing accurate answers. Come back soon for more trustworthy information.